2002
DOI: 10.1073/pnas.152152499
|View full text |Cite
|
Sign up to set email alerts
|

Global repression of exotoxin synthesis by staphylococcal superantigens

Abstract: Virulent Staphylococcus aureus strains typically produce and secrete large quantities of many extracellular proteins involved in pathogenesis. Such strains cause the classical staphylococcal lesion-local tissue destruction and aggressive inflammation accompanied by the massive influx of polymorphonuclear leukocytes, leading to the formation of pus. Most strains causing toxic shock syndrome, however, produce and secrete very small quantities of most exoproteins although they elaborate high levels of toxic shock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 33 publications
3
62
0
6
Order By: Relevance
“…Plasmid-carried ␤-lactamase fusions involving P hla , P tst , and P sspA were introduced into various strains and tested for ␤-lactamase activity during growth at pH 5.5 versus 7.5. The promoters for these three exoprotein genes were selected because, although postexponentially up-regulated by agr, they are regulated differentially by sar and sae (8,36,52; for a review, see the report of Novick 34). Results for the ␤-lactamase fusions are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid-carried ␤-lactamase fusions involving P hla , P tst , and P sspA were introduced into various strains and tested for ␤-lactamase activity during growth at pH 5.5 versus 7.5. The promoters for these three exoprotein genes were selected because, although postexponentially up-regulated by agr, they are regulated differentially by sar and sae (8,36,52; for a review, see the report of Novick 34). Results for the ␤-lactamase fusions are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prophage incorporation into the S. aureus results in increased ability of the bacteria to colonize the host tissue by ecological adaptation to human host, evasion from the immune system and production of virulence factors (5,7). A posasible contributor to this increased virulence is PantonValentine leukocidin (PVL), the prophage-encoded toxin responsible for necrotizing pneumonitis, which can be fatal within 24-48 hours, as recently described.…”
Section: Introductionmentioning
confidence: 92%
“…A posasible contributor to this increased virulence is PantonValentine leukocidin (PVL), the prophage-encoded toxin responsible for necrotizing pneumonitis, which can be fatal within 24-48 hours, as recently described. Superantigens are among the other important staphylococcal virulence factors; they are responsible for food poisoning, toxic shock syndrome (TSS) and necrotizing fasciitis (7).…”
Section: Introductionmentioning
confidence: 99%
“…Rather than contributing positively to T-cell toxicity, we found that the presence of the tst gene resulted in a decrease in the ability of a strain to lyse T cells. This could be explained by the findings of another study showing that TSST-1 has a global regulatory effect on exoprotein expression (17). To verify that TSST-1 and not some other factor in association with the gene for this protein was responsible for this, we compared the activity of a TSST-1-producing strain (strain RN4282 [7]) and an isogenic TSST-1 mutant (strain RN6938 [16]) (Fig.…”
mentioning
confidence: 98%